2020
DOI: 10.3390/cells9071739
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptors as Neuroinflammation Modulators: Role of A1 Agonists and A2A Antagonists

Abstract: The pathological condition of neuroinflammation is caused by the activation of the neuroimmune cells astrocytes and microglia. The autacoid adenosine seems to be an important neuromodulator in this condition. Its main receptors involved in the neuroinflammation modulation are A1AR and A2AAR. Evidence suggests that A1AR activation produces a neuroprotective effect and A2AARs block prevents neuroinflammation. The aim of this work is to elucidate the effects of these receptors in neuroinflammation using the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…It has been demonstrated that adenosine is a key anti-inflammatory mediator [50]. In the central nervous system, adenosine exerts its effects on inflammatory processes mainly through A1Rs and A2ARs [51]. A1Rs and A2ARs are expressed in astrocytes, oligodendrocytes, and microglia modulating inflammatory processes [50,52].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that adenosine is a key anti-inflammatory mediator [50]. In the central nervous system, adenosine exerts its effects on inflammatory processes mainly through A1Rs and A2ARs [51]. A1Rs and A2ARs are expressed in astrocytes, oligodendrocytes, and microglia modulating inflammatory processes [50,52].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, media were aspired and cells fixed with Fixative Solution for 15 min (high-purity 4% formaldehyde in PBS (Phosphate Buffered Saline), pH = 7.3). After that, they were washed 3 times with PBS and permeabilized with a Permeabilization Solution (0.5% Triton X-100) for 15 min [ 58 ]. They were washed again with PBS and incubated for 1 h with Blocking Buffer (3% BSA (Bovine Serum Albumin), fraction V delipidated in PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Following neuronal stress and damage, extracellular brain adenosine concentration is dramatically increased resulting in the promotion or attenuation of neuroinflammation. Many of the immunomodulatory effects of adenosine in the CNS are mediated by A 1 and A 2A AR subtypes [ 159 , 160 ], although recent evidence also points to the involvement of A 2B and A 3 ARs [ 161 , 162 ]. The expression of all four ARs has been detected in astrocytes, oligodendrocytes, and microglia [ 163 ].…”
Section: Neuroinflammationmentioning
confidence: 99%